Common bacterial dermatoses - Levy, J. A. (The Physician and Sportsmedicine, 2004)
Athletes competing in a wide variety of sports are at risk of contracting and spreading bacterial skin infections. Bacteria proliferate in environments of wet, macerated skin that is repeatedly abraded against competing athletes, equipment, clothing, or objects in the field of play. Common infections include impetigo, folliculitis, furunculosis, pitted keratolysis, and otitis externa. Diagnosis and treatment are often straightforward and vary little from care for nonathletes. However, knowledge of preventive strategies and return-to-play criteria, as outlined by the National Collegiate Athletic Association, are paramount for clinicians who care for competitive athletes.